Hydrolysis of Banana Stems with Sulfuric Acid Catalyst - Muhammad Dhafa Putra Alansyah; Caecilia Pujiastuti; Sani Sani; Suprihatin Suprihatin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Banana stems are agricultural waste with high lignocellulose content, making them a potential raw material for glucose production. This study aimed to determine the effect of sulfuric acid (H?SO?) concentration and hydrolysis time on the resulting glucose content. Prior to hydrolysis, delignification was performed using a 15% hydrogen peroxide (H?O?) solution. Hydrolysis was conducted at 100°C, varying H?SO? concentrations (1%, 3%, 5%, 7%, and 9%) and hydrolysis times (10, 15, 20, 25, and 30 minutes). The hydrolysis products were characterized using Fourier Transform Infrared (FTIR) spectroscopy, while the hydrolysate was analyzed using a refractometer to determine total solids (°Brix) as an estimate of sugar content. The results indicated that increasing both hydrolysis time and H?SO? concentration generally led to higher glucose yields. The highest glucose content, 15.2%, was achieved at an H?SO? concentration of 7% with a hydrolysis time of 20 minutes. Further increases in acid concentration or hydrolysis time did not result in higher estimated glucose levels, likely due to glucose degradation. The findings demonstrate that H?SO? concentration and hydrolysis time play a crucial role in the conversion of cellulose to glucose, highlighting the potential of banana stems as an alternative raw material for glucose production. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land